PERKEMBANGAN MASA BAYI - Anna Sari Hasibuan; Fina Nurhaliza; Bunga Sovia Erik (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2024)
Abstract. The baby's social emotional development must be a parent's main goal, because if social emotional development does not go well it will affect and hinder other developments such as psychomotor, emotional and other baby development. This research uses a method called critical review, which involves careful examination and evaluation of various sources of information, such as scientific journals, articles, and other media. The main goal of this approach is to improve readers' comprehension and interpretation skills in the field of early childhood development. Infancy is a time of rapid growth and change, infancy is a time of reduced dependency. The developmental tasks of infancy throughout the life span are, learning to eat solid food, learning to walk, learning to talk, learning to control the elimination of body waste, learning sexual differences and procedures, preparing to read, and learning to distinguish right from wrong, and starting to develop conscience. The development of patterns in the changes experienced by individuals since they were still in the womb over a certain life span, namely, weight, height, physical proportions, bones, muscles and fat, body shape, teeth, nervous system, and development of the sense organs. The psychological function of infancy is the period of formation of fundamental psychological patterns for eating, sleeping, and toileting, although the formation of these habits may not be complete by the end of infancy.